Introduction of Information Technology to Agricultural Product Chips UMKM - Abdul Haris Subarjo; Dedet Hermawan Setiabudi; Fajar Nugroho; Okto Dinaryanto; Mawar Kusumawardani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Agriculture contributes greatly to encouraging economic development, especially in countries that are highly dependent on this sector, such as Indonesia. In economic development, great attention is paid to the agricultural sector and its related industries, which are often referred to as agro-industry. With the development of information technology, there are opportunities to develop MSMEs in the agricultural sector. In order for community service activity partners to gain knowledge about the use of information technology, this activity is needed. Community service activities are carried out using a presentation method by the presenter. Community service activities introducing information technology for MSMEs for agricultural products went well and according to plan. There was an increase in the knowledge of activity participants.